Herausforderungen für die Demokratie: Überlegungen zu Skepsis, Kohärenz, Macht und Repräsentation. Vadian Lectures Band 7 - Meier Kressig, Marcel; Lindenau, Mathias (transcript, 2021)
Sceptics see the model of liberal democracy in crisis – an occasion to look at its problematic situations and challenges. With contributions by Jens Hacke, Georg Kohler, Jan-Werner Müller and Herfried Münkler.